Matricellular Protein CCN5 Gene Transfer Ameliorates Cardiac and Skeletal Dysfunction in mdx/utrn (±) Haploinsufficient Mice by Reducing Fibrosis and Upregulating Utrophin Expression - Song, Min Ho; Yoo, Jimeen; Oh, Jae Gyun; Kook, Hyun; Park, Woo Jin; Jeong, Dongtak (Frontiers in Cardiovascular Medicine, 2022)
Duchenne Muscular Dystrophy (DMD) is a genetic disorder marked by progressive muscle degeneration due to mutations in the dystrophin gene. Patients with DMD initially suffer from muscle weakness in their limbs during adolescence. With age, patients develop fatal respiratory and cardiac dysfunctions. During the latter stage of the disease, severe cardiac fibrosis occurs, compromising cardiac function. Previously, our research showed that matricellular protein CCN5 has anti-fibrotic properties. Therefore, we hypothesized that CCN5 gene transfer would ameliorate cardiac fibrosis and thus improve cardiac function in DMD-induced cardiomyopathy. We utilized mdx/utrn (+/-) haploinsufficient mice which recapitulate DMD-disease phenotypes and used an AAV.9 viral vector for CCN5 gene transfer. We evaluated the onset of cardiac dysfunction by echocardiography and determined our experimental starting point at 13- month-old mice. 8 weeks after CCN5 gene transfer, cardiac function was significantly enhanced and cardiac fibrosis was ameliorated. Additionally, running performance improved in CCN5 gene transferred mice. Furthermore, in sillico gene profiling analysis identified utrophin as a novel transcriptional target of CCN5. This was supplemented by a utrophin promoter assay and RNA seq analysis, which confirmed that CCN5 is directly associated with utrophin expression. Our results show that CCN5 may be a promising therapeutic molecule for DMD-induced cardiac and skeletal dysfunction.